2003
DOI: 10.1046/j.1365-3156.2003.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Seizure disorders among relatives of Kenyan children with severe falciparum malaria

Abstract: Summarypurpose The cause of seizures in children with falciparum malaria is unclear. In malaria endemic areas, children who develop severe falciparum malaria with seizures may have a genetically higher risk of epilepsy or febrile seizures. We used the history of seizures in relatives of children previously admitted with malaria to determine if there is evidence for a familial predisposition of seizures in children admitted with malaria and seizures or cerebral malaria.methods Family history of seizures were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 10 publications
1
19
0
Order By: Relevance
“…In studies of other CNS infections, the prevalence of epilepsy increases up to 20 years after infection, with the prevalence doubling between 5 and 15 years after the infection (21), so the prevalence in our cohort also may increase over time. However, previous studies in Kenya suggested that people with epilepsy have a higher risk of death (24,25), which may reduce the effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of other CNS infections, the prevalence of epilepsy increases up to 20 years after infection, with the prevalence doubling between 5 and 15 years after the infection (21), so the prevalence in our cohort also may increase over time. However, previous studies in Kenya suggested that people with epilepsy have a higher risk of death (24,25), which may reduce the effect.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that an association occurs between malaria and epilepsy but give no indication regarding causality. A preexisting susceptibility to epilepsy may result in a propensity to develop seizures during malaria (25). Alternatively, cerebral damage from severe malaria may result in an increased risk of epilepsy, or a combination of these factors may exist.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this finding, family studies in children from this community do provide strong evidence to support a genetic risk factor for acute seizures (Versteeg et al, 2003). It is likely that there are other susceptibility genes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the proportions of the types of epilepsy with grand mal being the most common type of seizures were similar to the findings from the Nigerian study and also to the observations made in Ethiopia and Uganda 2,3 . However the reporting of the predominance of grand mal epilepsy was not consistent in the studies on children as the findings by Kotsopoulos's 6 and et al in USA who found partial seizures to be more frequent in children than grand mal epilepsy. It is not immediately clear why grand mal prevailed over partial seizures in our setting and in other African based reports 2,3,9 .…”
Section: Discussionmentioning
confidence: 69%
“…Post febrile convulsions were found to be frequent especially among preterm babies in Finland 5 . Some of the febrile seizures were related to infections such as severe malaria and persisting after the initial episodes of malaria, a study observed in Kenya 6 . The second commonest neurological disorder in many settings is cerebral palsy whose global prevalence is about 2.5 per 1000 live births 1,7,8,9,10 .…”
Section: Introductionmentioning
confidence: 99%